Policymakers and mHealth: roles and expectations, with observations from Ethiopia, Ghana and Sweden - Catharina Barkman; Lars Weinehall (Taylor & Francis Group, 2017)
The rapid increase in mobile phone use and other telecommunication technologies in health care during the past decade has paved the way for optimism. mHealth (mobile health) initiatives need to be integrated into national health systems and priorities and fit into the system that the country has already invested in. Partnership between government, regional governments, health care systems, Community Health Workers, the private sector and universities is considered as a precondition for success. In turn, this requires strategic and integrative policy decisions on the national/regional level to be defined in the action plans as concrete steps. Decision makers are calling for scale-up plans to be in place even in the pilot phases. Hope is expressed that the initial joy and curiosity that new technology generates in the implementation phase will be transferred to routine work. Standards and a common technical architecture that enables interoperability and upscaling are key issues. Based on publications on policy and national strategies, this paper highlights some key areas for decision makers' role and expectations with regard to mHealth. The paper will also report some mHealth experiences from Ethiopia, Ghana and Sweden.